A prospective study of cost, patient satisfaction, and outcome of treatment of chalazion by medical and nursing staff. Issue 7 (1st July 2000) - Jackson, T L; Beun, L
Abstract : AIM: To study prospectively the outcome of conservative and surgical treatment of chalazia provided by medical and nursing staff. METHODS: During a 5 month recruitment period all patients attending a district general eye hospital for treatment of chalazion were included in the study. 129 patients (217 visits) with chalazia were seen by either a senior nurse or a trainee ophthalmologist (senior house officer, SHO) or both. Patients received either conservative treatment or eversion of the eyelid with incision and curettage. Patients were mailed a questionnaire asking them if their cyst had resolved and how they rated their treatment. Marginal cost analysis was used to determine the cost of treatment. RESULTS: The outcome of treatment could be determined in 170 of the 217 visits. Conservative treatment was successful for 29% of cysts while surgical treatment was successful for 72%. There was no significant difference in treatment outcome between nurse and SHO groups. Patients found nurse treatment acceptable with a high level of patient satisfaction. The marginal cost of treatment by a nurse was £9.91 per cyst compared with £12.10 for SHOs. There were no surgical complications and no evidence of malignancy in six biopsies. CONCLUSIONS: Surgical treatment of chalazion is safe and effective and successfully treats approximately three quarters of selected cysts. With conservative treatment approximately one third of selected chalazia will resolve within 3 months. Nurse treatment of chalazion is safe, effective, and acceptable to patients.